Integrating curricular and co-curricular endeavors to enhance student outcomes - Wankel, Charles; Wankel, Laura A.; Larose, Jordan; Greenheck, Quincy (Bingley : Emerald Group Publishing Limited, 2016)
Integrating Curricular and Co-Curricular Endeavors to Enhance Student Outcomes reports on a variety of innovative approaches taken in universities in a number of nations of their experience in bringing together learning in courses with learning in co- and extracurricular activities. Topics range from study abroad programs to service-learning. Also covered are community-based learning, cross-disciplinary collaborations, and peer-mentoring. This volume will introduce you to research and many interesting contexts, such as the U.S. Naval Academy, where promoting ethical leadership to cadets has been an important focus. Frame-breaking approaches, such as having university business students and circus performers collaborate, are explained within the context of the literature. The leveraging of Somali immigrant education programs for student learning is a stimulating activity that is also covered. Another inventive issue explored is the reformatting of traditional co-curricular transcripts to reflect a wider indication and measure of students' skills and abilities.
Includes biographical references.
Print version record
Keywords: Education -- Curricula; Education -- Curricula; Universities